Kelimpahan Zooplankton sebagai Indikator Kesuburan Perairan di Rawa Banjiran Desa Sedang Kecamatan Suak Tapeh Kabupaten Banyuasin - Yusanti, Indah Anggraini (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
The study of zooplankton abundance as an indicator of water fertility in the Banjiran swamp in the Sedang Village of Suak Tapeh Subdistrict, Banyuasin Regency was conducted in July to August 2017. The zooplankton sampling method was carried out at 3 (three) stations namely nebong kuning swamp station (station 1), poron swamp (station 2) and banan swamp (station 3) using purposive random sampling method. Data obtained in this study include data on zooplankton composition, zooplankton abundance index and zooplankton dominance index. While the data analysis was carried out descriptively. The results of zooplankton identification obtained during the study found 8 (eight) genera of zooplankton consisting of 3 (three) classes, namely Monogononta 1 genus, Mastigophora 5 genus and Ciliate 2 genus. The highest zooplankton abundance was found at station 1 kuning nebong swamp and banan swamp with an average value of 1.75 ind / L and 1,5 ind/L indicating the level of fertility of the floodwaters belongs to the mesotrophic category and the lowest at station 2 poron swamp with an average value of 0.92 ind / L indicating the level of fertility of the floodwaters in the Sedang village of Suak Tapeh Subdistrict, Banyuasin Regency belongs to the oligotrophic category.